On-court throwing activity of male handball players during the European Championship 2020 - Basilio Pueo; Juan Tortosa-Martínez; Luis Chirosa-Rios; Carmen Manchado (Termedia Publishing House, 2022)
The aim of this study was to investigate the on-court throwing activity in regards to playing positions, throwing zones on the court and throwing velocity category during the male European Championship 2020. A local positioning system with microsensors placed both in the shirts of the players and inside the ball itself was used. In total, 6568 throws were retrieved for analysis from the entire tournament. Results showed that first-line players (wings and line players) used their natural zone more to throw (65% left wing, 60% right wing, and 97% line player), showing higher effectiveness from there (p < 0.05). Second lines players distributed more of their throws (45% left back, 50% right back and 32% center back in their natural zones) giving priority to the throws in 6 m, where they showed higher effectiveness (p < 0.05), or between the lines. Considering all players, shots from nearby and intermediate areas corresponded to 83% of the shots showing higher efficiency (p ~100 km/h) from these furthest areas. Throwing velocity and effectiveness by throwing zones and positions was not significantly modified over the three rounds of the tournament (p > 0.05), indicating no effect of possible fatigue. A higher team ranking was associated with higher throwing efficiency but only for wing players. The results of this research could help handball coaches to better adjust training programs for the improvement of throwing velocity and its transfer to the competition.